The socioeconomic consequences of optic neuritis with and without multiple sclerosis: a controlled national study. (20th July 2012) - Jennum, P.; Frederiksen, J. L.; Wanscher, B.; Kjellberg, J.
<x xml:space="preserve">Abstract</x> Objectives Optic neuritis (ON) often precedes multiple sclerosis (MS). MS is associated with a significant socioeconomic burden. However, the burden of ON with and without MS before and after its diagnosis has never been calculated. Methods Using complete national records from the Danish National Patient Registry (1998–2006), we identified 1677 patients with ON and compared them with 6708 randomly selected citizens matched for age, sex and geography. A societal perspective is taken towards the cost analyses. Costs included in the analysis are those of the health sector, including all contacts with primary and secondary sectors, and the use and costs of drugs. Productivity losses included labour supply and income. All social transfer payments were also calculated. Results Patients with ON had higher rates of contact with healthcare services, medication use and income from employment, all of which incurred a higher socioeconomic cost. Employed patients had lower income than control subjects. The total annual excess costs relative to matched controls were €3501 for ON patients and €9215 for patients with a dual diagnosis of ON and MS. The ON and ON+MS patients received an annual mean excess social transfer income of €1175 and €4619. ON/ON+MS patients presented social and economic consequences up to 8 years before diagnosis, and these increased after the diagnosis was established. Conclusions ON, especially if combined with a diagnosis of MS, has a significant socioeconomic consequence for the individual patient and for society. Productivity losses are a far more important economic factor than health sector costs.